A critical review on the variations in anodization parameters toward microstructural formation of TiO2 nanotubes. Issue 4 (16th August 2021) - David, T. Manovah; Dev, Priya Ranjan; Wilson, P.; Sagayaraj, P.; Mathews, Tom
Abstract: Over the past couple of decades (2001–2020), titania (TiO2 ) nanotubes (NTs) have been prepared by anodization techniques. The architecture of TiO2 NTs is predominantly dependent on the potential, current density, electrolyte and time, in addition to other few minor factors. This review is about the state‐of‐the‐art formation of TiO2 NTs involving anodization technique. In fact, the principal motive is to briefly discuss the slight variations involved within the anodization technique in terms of applied potential and/or applied current density and the resultant outcome. An initial overview of the technique is given so as to understand the beauty of the reactions when variations are incorporated. A minute alteration in the conventional anodization technique results in the formation of highly different morphological features. There are about 30 different miniscule modifications in the anodization processes that have been reported, thus, far. The review primarily introduces and outlines the various anodization techniques involved in growing TiO2 NTs and the consequent variations arising from these introduced variations. This review is a tribute to the bountiful and fruitful researches based on modifying anodization that was conducted in the recently passed bi‐decades.